Surface Modification with Particles Coated or Made of Polymer Multilayers - Konstantinos T. Kotoulas; Jack Campbell; Andre G. Skirtach; Dmitry Volodkin; Anna Vikulina (MDPI AG, 2022)
The coating of particles or decomposable cores with polyelectrolytes via Layer-by-Layer (LbL) assembly creates free-standing LbL-coated functional particles. Due to the numerous functions that their polymers can bestow, the particles are preferentially selected for a plethora of applications, including, but not limited to coatings, cargo-carriers, drug delivery vehicles and fabric enhancements. The number of publications discussing the fabrication and usage of LbL-assembled particles has consistently increased over the last vicennial. However, past literature fails to either mention or expand upon how these LbL-assembled particles immobilize on to a solid surface. This review evaluates examples of LbL-assembled particles that have been immobilized on to solid surfaces. To aid in the formulation of a mechanism for immobilization, this review examines which forces and factors influence immobilization, and how the latter can be confirmed. The predominant forces in the immobilization of the particles studied here are the Coulombic, capillary, and adhesive forces; hydrogen bonding as well as van der Waal's and hydrophobic interactions are also considered. These are heavily dependent on the factors that influenced immobilization, such as the particle morphology and surface charge. The shape of the LbL particle is related to the particle core, whereas the charge was dependant on the outermost polyelectrolyte in the multilayer coating. The polyelectrolytes also determine the type of bonding that a particle can form with a solid surface. These can be via either physical (non-covalent) or chemical (covalent) bonds; the latter enforcing a stronger immobilization. This review proposes a fundamental theory for immobilization pathways and can be used to support future research in the field of surface patterning and for the general modification of solid surfaces with polymer-based nano- and micro-sized polymer structures.